Liquor Bilirubin Levels and False Prediction of Severity in Rhesus Haemolytic Disease - Pridmore, B. R. (1972)
Liquor bilirubin levels gave a false prediction of outcome for the fetus in 80 out of 716 rhesus-sensitized women referred for treatment during 1965-9. Trauma caused by amniocentesis seemed to be responsible for an increase in the severity of immunization in a significant proportion of cases. In addition, contamination of liquor samples by plasma, particularly fetal plasma, completely invalidated liquor bilirubin estimations. Errors in estimation of gestational length were also found to be associated with misleading results and a poor fetal prognosis.